Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2016)
A dataset containing 298 species occurrences available in GBIF matching the query: { "TaxonKey" : [ "is Nymphaea mexicana Zucc." ] } The dataset includes 298 records from 50 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001773-160822134323880/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences